Is Fun For Wellness Engaging? Evaluation of User Experience of an Online Intervention to Promote Well-Being and Physical Activity - Scarpa, Michael P.; Prilletensky, Isaac; McMahon, Adam; Myers, Nicholas D.; Prilleltensky, Ora; Lee, Seungmin; Pfeiffer, Karin A.; Bateman, André G.; Brincks, Ahnalee M. (Frontiers in Computer Science, 2021)
Online well-being interventions demonstrate great promise in terms of both engagement and outcomes. Fun For Wellness (FFW) is a novel online intervention grounded in self-efficacy theory and intended to improve multidimensional well-being and physical activity through multi-modal methods. These strategies include capability-enhancing opportunities, learning experiences such as games, video vignettes, and self-assessments. RCT studies have suggested that FFW is efficacious in improving subjective and domain-specific well-being, and effective in improving mental health, physical health, physical activity, and self-efficacy in U.S. adults who are overweight and in the general population. The present study uses qualitative and quantitative user experience data collected during two RCT trials to understand and evaluate engagement with FFW, its drivers, and its outcomes. Results suggest that FFW is enjoyable, moderately engaging, and easy to use; and contributes to positive outcomes including skill development and enhanced confidence, for both overweight individuals and the general adult population. Drivers of engagement appear to include rewards, gamification, scenario-based learning, visual tracking for self-monitoring, ease of use and simple communications, and the entertaining, interactive nature of program activities. Findings indicate that there are opportunities to streamline and simplify the experience. These results can help improve FFW and contribute to the science of engagement with online interventions designed to improve well-being.